Dynamic Programming and Bayesian Inference, Concepts and Applications - Carbonari Alessandro; Vaccarini Massimo; Giretti Alberto et al; InTech
La programacin̤ dinm̀ica y la inferencia bayesiana se han desarrollado de forma intensiva y extensiva durante los l͠timos aǫs. Debido a estos avances, el interš en ellas y sus aplicaciones ha crecido de modo significativo en todos los niveles de las matemt̀icas. El props̤ito de este libro es mostrar algunas de tales aplicaciones.El documento est ̀conformado por los siguientes capt̕ulos:Bayesian Networks for Supporting Model Based Predictive Control of Smart Buildings Integration of Remotely Sensed Images and Electromagnetic Models into a Bayesian Approach for Soil Moisture Content Retrieval: Methodology and Effect of Prior Information Optimizing Basel III Liquidity Coverage Ratios Risk-Constrained Forward Trading Optimization by Stochastic Approximate Dynamic Programming Using Dynamic Programming Based on Bayesian Inference in Selection Problems